Reproductive trade-off in male Antarctic krill, Euphausia superba - Patti Virtue; Nichols, P; Nicol, S; Hosie, G (1996)
Freshly caught male and female Euphausia superba from the same swarm exhibited different rates of mortality subsequent to capture. Mortality was significantly higher for reproductive males (100%, n = 68) than for females (3%, n = 186) within the first 3 d of capture. Total lipid and triacylglycerol levels in male, female and juvenile Euphausia superba were analysed and compared. All reproductive male krill analysed from this swarm had low lipid levels (1 to 3% dry weight) with negligible triacylglycerol stores (0 to 2% of total lipid). Somatic lipid stores in female and juvenile krill ranged from 8 to 30%, of which up to 40% was triacylglycerol. The levels of algal sterols in the digestive gland of males, females and juveniles indicate that all krill had been feeding recently. An analysis of the sex ratio of krill catches derived from data collected over seven summers from the Prydz Bay region showed a decrease in the proportion of males with increasing size. There was a sharp decline in numbers of male krill once they attained a length of 51 to 55 ram. Low lipid levels in redroductive male krill may be due to reproductive costs. The resulting low storage-lipid levels are accompanied by high mortality in male krill.